2014
DOI: 10.3399/bjgp15x683149
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of older people engaging in nurse-led cardiovascular prevention programmes: a qualitative study in primary care in the Netherlands

Abstract: BackgroundCardiovascular prevention programmes are increasingly being offered to older people. To achieve the proposed benefits, adherence is crucial. Understanding the reasons for adherence and non-adherence can improve preventive care.AimTo gain insight into what motivates older people living in the community to partake in a cardiovascular prevention programme, and reasons for subsequent continuation or withdrawal.Design and settingQualitative study of current and former participants of the ongoing ≥6 year P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…Specifically, older adults felt supported and did not feel threatened in such an informal and welcoming space. This is in keeping with other similar research showing that talking down to older people creates a barrier to adopting healthier lifestyle practices (Ligthart et al, 2015;Ryan, Hummert, & Boich, 1995;Woolhead, Calnan, Dieppe, & Tadd, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, older adults felt supported and did not feel threatened in such an informal and welcoming space. This is in keeping with other similar research showing that talking down to older people creates a barrier to adopting healthier lifestyle practices (Ligthart et al, 2015;Ryan, Hummert, & Boich, 1995;Woolhead, Calnan, Dieppe, & Tadd, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, engaging older adults in an informal and welcoming manner to discuss ideas in a supportive and non-threatening manner is appealing to this age range. This is in keeping with other research around engaging older adults in health and lifestyle discussions whereby 'talking down' to older persons created a barrier to encouraging them to adopt healthier lifestyle practices (Ligthart et al, 2015;Ryan, Hummert, & Boich, 1995;Woolhead, Calnan, Dieppe, & Tadd, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…It may be the personal attention from the intervention nurse was responsible for these differential findings. Findings from qualitative research in preDIVA completers and dropouts that showed that the personal approach of the nurse was an important motivator to keep participating corroborated this . The greater risk of dropout in people with greater disability in the intervention group may indicate that even this low‐intensity intervention became too demanding for more physically impaired participants.…”
Section: Discussionmentioning
confidence: 78%
“…26 Recently Ligthart et al reported that regular check-ups, a coaching approach, and a personal relationship with the patient facilitated engagement of older people in long-term preventive consultations. 27 Congruent with the present finding that quality of life is the ultimate aim of secondary cardiovascular preventive care in older age, Drewes and Frank also describe a shift in treatment goals in older patients away from prolonging life to controlling symptoms, or maximising function, and individualised patient-centred goal setting. 28,29 Implications for research and practice To facilitate implementation, the present authors recommend development of specific (attenuated) targets and specific charts showing benefits and risks for older people, and to incorporate these into current guidelines for secondary cardiovascular prevention.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%